ANALISIS FINANSIAL USAHA IKAN ASAP PINEKUHE DI KABUPATEN KEPULAUAN SANGIHE - Bue, Danny Rofiyanto; Andaki, Jardie A.; Pangemanan, Jeannette F. (Universitas Sam Ratulangi, 2015)
Abstract Pinekuhe smoked fish business is often faced with the lack of capital and lack of management in an effort to increase production. The lack of efficient production processes in the suspect is a problem that arises due to ignorance of the fishermen in regulating the financial factors of production, that the maximum benefit is not achieved. Based on these things, then the problem can be formulated as follows: What are the factors that affect the business financial analysis of smoked fish Pinekuhe in the rate of business profits smoked fish Pinekuhe in Tahuna Sangihe Islands Regency. As well as how to optimize financial Pinekuhe smoked fish in order to achieve the maximum rate of profit. The purpose of this study, namely 1) make a financial analysis of smoked fish business Pinekuhe Tahuna on Sangihe Islands Regency and 3) to study the rate of profit on Pinekuhe smoked fish business. Basic research will be used is a case study, the research form by studying a particular case in which the object is limited (Widi, 2010). The results showed that the sale of smoked fish